2007
DOI: 10.1007/s00128-007-9324-2
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Airborne Polyfluorinated Telomers in Keihan Area, Japan

Abstract: Perfluorooctanoate (PFOA) are environmental contaminants posing special public health concerns because of their long-term persistence and bioaccumulation in the environment. Fluorotelomer alcohols are volatile and may undergo long-range transport. Air samples were collected at five sites in the Keihan area, Japan: Sakyo, Morinomiya and three sites in Higashiyodogawa. Except for Higashiyodogawa, the highest concentrations of fluorotelomer alcohols (FTOHs) were for 8:2 FTOH (median 447 pg m(-3)) followed by 10:2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 9 publications
5
21
0
Order By: Relevance
“…In this work, two fluorotelomer acrylates, 8:2 FTAC and 6:2 FTAC, were determined at relatively low levels with ranges of <0.2-4.4 and <0.9-1.2 pg m −3 , respectively. These results are two to five times lower than those reported in the North Sea and at an urban site of Hamburg (Dreyer and Ebinghaus 2009) and in the Asia-Pacific region (Li et al 2011), and 3 orders of magnitude lower than those reported in Japan (Oono et al 2008). FTACs are monomers used in the manufacturing of fluorotelomer-based polymers.…”
Section: Resultsmentioning
confidence: 62%
“…In this work, two fluorotelomer acrylates, 8:2 FTAC and 6:2 FTAC, were determined at relatively low levels with ranges of <0.2-4.4 and <0.9-1.2 pg m −3 , respectively. These results are two to five times lower than those reported in the North Sea and at an urban site of Hamburg (Dreyer and Ebinghaus 2009) and in the Asia-Pacific region (Li et al 2011), and 3 orders of magnitude lower than those reported in Japan (Oono et al 2008). FTACs are monomers used in the manufacturing of fluorotelomer-based polymers.…”
Section: Resultsmentioning
confidence: 62%
“…29 Concentrations of FTAs were generally <100 pg m À3 , except at Higashiyodogawa, in Osaka City, Japan where the highest value of 2950 pg m À3 was detected. 24 In this study, the concentrations of 6:2 FTA and 8:2 FTA ranged from ND-3.4 pg m À3 and ND-15 pg m À3 with frequencies of detection of 24% and 93%, respectively. Overall, these results are in the same range as previous studies (see Table S6).…”
Section: ' Introductionmentioning
confidence: 55%
“…Specifically, correlations were high (r > 0.90, p < 0.01) between 8:2 FTOH, 10:2 FTOH, and 12:2 FTOH, as observed at other sites in the world. 24,25 However, 4:2 FTOH and 6:2 FTOH did not show significant correlation with other FTOHs. This implies that these FTOHs are sourced from the different products containing the different FTOH composition in Asia.…”
Section: Articlementioning
confidence: 74%
“…FTOHs are currently produced and used as intermediates for the synthesis of coatings, polymers, inks, adhesives, waxes, and so on. Oono et al [41,42] reported that the airborne levels of several FTOHs were significantly higher in the Kyoto-Osaka area than in other areas. Taken together, the higher levels of airborne PFOA in the Kyoto-Osaka area may be caused by the high levels of FTOHs in the air.…”
Section: Distributions Of Pfoa and Pfos In Outdoor Air And Indoor Dusmentioning
confidence: 98%